ANALYSIS OF THE IMPLEMENTATION OF BLOCKCHAIN TECHNOLOGY IN SHARIA BANKING TRANSACTION TRANSPARENCY - Fitria; Dian Rahmita Sari (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyse the implementation of blockchain technology to improve the transparency of Islamic banking transactions. The research method uses a qualitative approach, namely a literature analysis study (library research), with content analysis techniques on various credible sources such as reference books, indexed scientific journals (Scopus, Sinta, Google Scholar), financial reports, and official documents related to policies and regulations in Islamic banking. The focus of this research is to explore the potential of blockchain in strengthening the principles of transparency, accountability, and operational efficiency, and to identify the challenges faced in its implementation in the Islamic banking sector. The results show that blockchain technology is able to minimise the risk of fraud, improve operational efficiency through a decentralised, secure, and immutable transaction recording system, and strengthen customer trust. Innovations such as smart contracts, Islamic DeFi, and digital sukuk open up opportunities for the development of Islamic financial products that are more adaptive and inclusive. However, there are several challenges including regulatory limitations, technological infrastructure readiness, low digital literacy, and the need to adjust blockchain to sharia principles, especially regarding the potential for usury, gharar, and maisir. This research recommends collaboration between regulators, Islamic financial institutions, and technology providers in designing a legal framework that is compliant with sharia principles and supports system transparency. The key to successful blockchain implementation is increased digital literacy among industry players and the public, strengthened regulation, and investment in technological infrastructure. This research also emphasises the importance of further exploring the impact of blockchain on Islamic financial inclusion and customer data protection to build a more transparent, fair and inclusive Islamic banking system.